(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
In recent years, an increasing number of scholars has suggested that the zoonyms recurrent in the recipient position in some Thebes tablets could be reasonably interpreted as ritual titles; these may refer to persons dressed as animals and engaged in some kind of cult activity. Looking for iconographic parallels of animal masks and masquerades in the Aegean bronze age, some authors have turned their attention to a number of homosomatic hybrids that populate Minoan and Mycenaean glyptic. The latter have been interpreted as reflecting real-life practices and actual performances of enacted transfiguration, during which people may have been garbed as lions, bulls, agrimi, stags, and so forth, using masks and hides, for symbolic, even shamanistic, purposes. The present study deals with the complex issue of hybridity with reference to a specific iconographic type, the «Tiermenschlicher Akrobaten» or «somersaulting hybrid man». The analysis of these images takes into account their circulation and the social practices to which they are associated, discussing the possibility that they may have played multiple roles in ritual, corporeal, social, and political narratives.